2014
DOI: 10.5578/tt.7902
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of arsenic and cadmium levels in biological samples of cases with lung cancer

Abstract: The evaluation of arsenic and cadmium levels in biological samples of cases with lung cancer Introduction: Chronic exposure to the toxic metals plays an important role among the causes of lung cancer beside of smoking We g. aimed to evaluate the association between the histopathologic type of lung cancer and arsenic and cadmium levels in biological samples. mp Materials and Methods: This study in a single center was conducted through the years 2009-2013, including 72 patients with lung l cancer, within a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Despite the limited number of studies showing that Cd has no association with lung cancer, recent studies have identified an increased risk of lung cancer in the population exposed to Cd. 109,110 It has been reported that Cd levels in 24-hour urine are positively associated with both lung cancer and total cancer risk.…”
Section: And Lungmentioning
confidence: 99%
“…Despite the limited number of studies showing that Cd has no association with lung cancer, recent studies have identified an increased risk of lung cancer in the population exposed to Cd. 109,110 It has been reported that Cd levels in 24-hour urine are positively associated with both lung cancer and total cancer risk.…”
Section: And Lungmentioning
confidence: 99%
“…In Beder's study, among 1068 pneumoconiosis patients, p-type and q-type opacities were the most common in 43.9% of cases, respectively. Type C opacities were found in 2.7% of cases, while type B and type A opacities were found in 2% of cases each [16]. Şakar et al reported the detection of p-and q-type opacities in 24 patients with pneumoconiosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by İçmeli, which evaluated disability rates in coal worker pneumoconiosis cases, found that the average working time in the mines was 23 years [11]. Similarly, Beder's study on pneumoconiosis cases whose liability period expired revealed an average working period of 23.51 years [16]. These differences in working time can be attributed to the predominance of CWP patients in the studies of Liman, İçmeli, and Beder, while the majority of patients in our study had a diagnosis of silicosis.…”
Section: Discussionmentioning
confidence: 99%